Implementação e mitigação de ataques cibernéticos em sistemas SCADA - Figueiredo, Camilla Emilly Jácome Ferreira de (2021)
In the midst of the reality in which we live, in which technology becomes increasingly present in society, the smart grid has emerged to offer numerous benefits to the industry and facilitate the distribution of energy on a large scale. However, these smart grids - along with their Supervisory Control and Data Acquisition Systems (SCADA) - have numerous weaknesses, being exposed to various cyber attacks that can cause unbearable losses. Given this, inserted in the context of network security in cyber-physical systems, this present work investigates vulnerabilities in the communications between the devices present in SCADA and, through the execution of attacks (which, if successful, can have any purpose, from financial to lethal damage), aims to penetrate and compromise the services provided by a smart grid and successively propose mitigations to make this system more secure. For this purpose, aiming at obtaining a qualitative analysis, exploratory bibliographic research was used as well as practical experimental research as a methodology, presenting a systematic mapping in the area in question and the implementation of the following cyber attacks: Man-in-the-Middle, TCP Syn Flood, ARP Attack and Reflection Attack, the latter being absent in previous works. As a result of this and through the studies carried out and the effectiveness of the attacks worked on here, the system's vulnerabilities are explored in real scenarios and the importance of such contributions and countermeasures are reiterated.